The Impact of HBV Infection and Barriers to HBV-related Care in Asian Americans - Hu, MD, Ke-Qin (North American Journal of Medicine and Science, 2011)
Hepatitis B virus (HBV) infection is one of the major global public health problems. The prevalence of HBV infection is very high in Asian Americans (ASAMs), accounting for more than 50% cases in this country. Many of these individuals may not be aware of this infection, due to under utilization of HBV screening and community education. A high incidence of HBV infection has also been associated with lower knowledge and access to hepatitis B care in ASAMs. Studies have identified many health provider-, patient-, and resource-related factors that contribute to barriers of HBV care in this special population. Understanding these will help us in developing multiple approaches to effectively reduce the disparity and improve the outcomes of HBV infection in the ASAMs.